Phytoremediation of Soil Contaminated With Copper and Zinc from Pig Waste - Wang, Yan (2005)
Copper (Cu) and Zinc (Zn) are two elements of great concern due to their potential toxicity to plants and/or animals. Most pig farmers in Malaysia fed two to three folds of the recommended Cu and Zn to their animals. Only about 15% of the dietary Cu and Zn were apparently digested while the remaining 85% were excreted mainly via the feces. It is estimated that 390 tons of Cu and 303 tons of Zn are being excreted annually by approximately two million pigs in Malaysia. Appropriate management of the pig waste is, therefore, essential to ensure that these heavy metals do not pollute the environment.